Determining Proportion of Exfoliative Vaginal Cell during Various Stages of Estrus Cycle Using Vaginal Cytology Techniques in Aceh Cattle - Tongku N. Siregar; Juli Melia; Rohaya; Cut Nila Thasmi; Dian Masyitha; Sri Wahyuni; Juliana Rosa; Nurhafni; Budianto Panjaitan; Herrialfian (Veterinary Medicine International)
The aim of this study was to investigate the period of estrus cycle in aceh cattle, Indonesia, based on vaginal cytology techniques. Four healthy females of aceh cattle with average weight of 250–300 kg, age of 5–7 years, and body condition score of 3-4 were used. All cattle were subjected to ultrasonography analysis for the occurrence of corpus luteum before being synchronized using intramuscular injections of PGF2 alpha 25 mg. A vaginal swab was collected from aceh cattle, stained with Giemsa 10%, and observed microscopically. Period of estrus cycle was predicted from day 1 to day 24 after estrus synchronization was confirmed using ultrasonography analysis at the same day. The result showed that parabasal, intermediary, and superficial epithelium were found in the vaginal swabs collected from proestrus, metestrus, and diestrus aceh cattle. Proportions of these cells in the particular period of estrus cycle were 36.22, 32.62, and 31.16 (proestrus); 21.33, 32.58, and 46.09 (estrus); 40.75, 37.58, and 21.67 (metestrus); and 41.07, 37.38, and 21.67 (diestrus), respectively. In conclusion, dominant proportion of superficial cell that occurred in estrus period might be used as the base for determining optimal time for insemination.